(untitled) (Jurnal Teknik Elektro, 2016)
Transformer insulator is an important part in electrical devices because it can muffle breakdown voltage and current interference. Refinement of transformer insulator can be done by replacing previous insulator such as recondition of electrical coils resistance and transformer oil. Recondition of transformer should be donein insulator of electrical coil especially if this coil was burned before. This breakage can causeno voltage in one of transfomer phase. Reparation which should bedone is substitution of secondary electrical coil and oil transformer.